Age, sex and seasonal variation in the shape and size of erythrocytes of the alpine accentor, Prunella collaris (Passeriformes: Prunellidae). Issue 1 (1st January 2017) - Janiga, M.; Haas, M.; KufelovÃ¡, M.
Abstract: The aim of our study was to analyse red blood cells from the high-altitude avian species alpine accentor ( Prunella collaris ). We caught 79 alpine accentors in the High Tatra Mountains (the West Carpathians, Slovakia) from 2001 to 2008. Blood samples were collected from the vena ulnaris cutanea . The cells and nuclei of juveniles tend to be wider and larger while adults, especially males, tend to have elongated (narrow) cells. The largest erythrocytes were found in winter and the smallest in summer, in June. Red blood cells with larger, elongated nuclei but overall smaller in size occurred at the beginning and the end of the breeding season, while larger, rounded cells with smaller nuclei were found in the middle of the breeding season. This kind of reshaping of erythrocytes of alpine accentors in summer is probably a response to hypoxia and elevated summer temperature in high mountains. As regards the length/width ratio, in August and September, erythrocytes were more elongated (both cell and nucleus) than in the other months. This study is probably the first assessment of seasonal effects on size and shape of red blood cells of bird species permanently living and breeding at high altitudes of the Palearctic mountains.